Plastic films in food packaging matertials, technology and applications - Ebnesajjad, Sina (PDL handbook series, 2013)
"This new handbook is a combination of new material and updated chapters, chosen by Dr. Sina Ebnesajjad, from recently published books on this subject. Plastic Films in Food Packaging offers a practical handbook for engineers, scientists and managers working in the food packaging industry, providing a tailor-made package of science and engineering fundamentals, best practice techniques and guidance on new and emerging technologies. By covering materials, design, packaging processes, machinery and waste management together in one book, the authors enable the reader to take a lifecycle approach to food packaging. The Handbook addresses questions related to film grades, types of packages for different types of foods, packaging technologies, machinery and waste management. Additionally the book provides a review of new and emerging technologies. Two chapters cover the development of barrier films for food packaging and the regulatory and safety aspects of food packaging. Essential information and practical guidance for engineers and scientists working at all stages of the food packaging lifecycle: from design through manufacture to recycling. Includes key published material on plastic films in food packaging, updated specifically for this Handbook, and new material on the regulatory framework and safety aspects. Coverage of materials and applications together in one handbook enables engineers and scientists to make informed design and manufacturing decisions."--Resumé vydavatele